Performance Evaluation and Field Characterization of the Sifang Mini Rice Combine Harvester - Amponsah, S.K.; Addo, A.; Dzisi, K.A.; Moreira, J.; Ndindeng, S.A. (American Society of Agricultural and Biological Engineers, 2017)
Abstract. Performance of a Sifang mini rice combine, originally developed in China, was evaluated under local farmer field conditions in Benin. Results from field evaluation show that the combine worked satisfactorily on less dense rice fields with minimal weeds at grain moisture contents between 19.1% and 20.1% w.b. on soils with moisture content from 23% to 33% d.b. while causing no significant changes to soil physical properties. With harvesting speed ranging from 0.8 to 4.5 km/h, the harvester had a field capacity of 0.10 to 0.39 ha/h and consumed fuel of up to 11 L/ha while having track slip of 6% to 9%. Harvesting using 2- and 1-L gear offered the best efficiency for IR841 and Nerica L20 rice varieties, respectively. As harvesting speed increased, harvesting efficiency decreased and crop throughput increased irrespective of rice variety. The combine produced low mechanical grain damage with total grain loss ranging from 1.43% to 4.43% and 1.85% to 5.6% for the IR841 and Nerica L20 rice varieties, respectively. At an investment cost of US$5000 and hiring at US$10 per h, owning the mini combine harvester becomes profitable after 342 h of machine use; equivalent to approximately 133 ha of paddy field harvested at a harvesting capacity of 0.39 ha/h. Further testing of the combine under a wide range of crop and soil conditions across different agro-ecological zones and economic comparison with manual harvesting is recommended. This would offer smallholder farmers diverse options of rice harvesting mechanization to facilitate future adoption of improved technologies. Keywords: Crop throughput, Field capacity, Field efficiency, Grain loss, Mini rice combine, Sifang.